Nursing care in a Long Stay Institution for the Elderly: perceptions of religious elderly women (Research, Society and Development, 2019)
The present study aims to analyze the perceptions of religious elderly women about nursing care in a Long Stay Institution for the elderly in the interior of Rio Grande do Sul, Brazil. This is a descriptive and exploratory study, with a qualitative approach, carried out with ten participants residing in the mentioned institution. The data collection was performed through interviews, and the findings were analyzed with the Bardin Content Analysis (2011) approaches. With the result, it is understood that the nursing team and the religious caregivers are contributing and assisting a holistic and integral assistance to the elderly religious. According to the statements of the participants, there is a relationship of care and trust between the team and the elderly women, allowing a quality and humanized service to be performed. Thus, it is understood that the nursing team performs a humanized care that is in keeping with the needs of the elderly women, strengthening the bond and making healthy the coexistence in the institution.